2015
DOI: 10.1161/circep.115.003155
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Cardiac Na + Channel Conformations Reveals Molecular Pathologies of Inherited Mutations

Abstract: Background Dysregulation of voltage-gated cardiac Na+ channels (NaV1.5) by inherited mutations, disease-linked remodeling, and drugs causes arrhythmias. The molecular mechanisms whereby the NaV1.5 voltage-sensing domains (VSDs) are perturbed to pathologically or therapeutically modulate Na+ current (INa) have not been specified. Our aim was to correlate INa kinetics with conformational changes within the four (DI-DIV) VSDs to define molecular mechanisms of NaV1.5 modulation. Method and Results Four NaV1.5 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 31 publications
7
68
0
Order By: Relevance
“…Tracking DIV-VSD conformation during the steady-state inactivation protocol reveals a striking correlation between DIV-VSD activation and closed-state inactivation ( Fig. 2) (Varga et al, 2015), similar to previous findings in Nav1.4, where DIV-VSD activation was found to be the rate limiting step of channel inactivation (Capes et al, 2013).…”
Section: Cardiac Sodium Channel Na V 15supporting
confidence: 89%
See 4 more Smart Citations
“…Tracking DIV-VSD conformation during the steady-state inactivation protocol reveals a striking correlation between DIV-VSD activation and closed-state inactivation ( Fig. 2) (Varga et al, 2015), similar to previous findings in Nav1.4, where DIV-VSD activation was found to be the rate limiting step of channel inactivation (Capes et al, 2013).…”
Section: Cardiac Sodium Channel Na V 15supporting
confidence: 89%
“…We found that the A735V mutation dramatically shifted DII-VSD activation to depolarized potentials, while the G752R mutation significantly slowed DII-VSD kinetics ( Fig. 3B) (Varga et al, 2015). The ability of the channel to open at potentials negative to the DII-VSD activation in A735V and at times prior to activation in G752R, confirmed our initial suspicion that the DII-VSD is a facilitator of activation, but is not absolutely required for opening.…”
Section: Cardiac Sodium Channel Na V 15supporting
confidence: 74%
See 3 more Smart Citations